Evaluasi Digital Berbasis Kahoot! untuk Mengukur Kemampuan Berpikir Kritis dan Meningkatkan Motivasi Belajar - Ramdiani , Rani; Nurhikmayati, Iik; Sudianto, Sudianto (Polinomial : Jurnal Pendidikan Matematika, 2025)
This research aims to analyze how technology integration, especially the use of Kahoot! application in the learning evaluation process can be used to measure critical thinking skills while increasing students' learning motivation. This research uses a type of development research or Research & Development (R&D) with the ADDIE model. The stages include Analysis, Design, Development, Implementation, and Evaluation. The research instruments included test questions, interviews, expert validation sheets, and practicality sheets. The results showed that this product has a high level of validity, with an average assessment of media experts at 92.8% and material experts at 85%. The practicality test results show that Kahoot! has a high level of practicality with an average practicality from teachers of 89.75% and practicality from students of 87.67%. The results of the analysis showed that the N-Gain value was in the medium improvement category, which amounted to 51%. The conclusion of this study is that technology integration through the use of Kahoot! application in learning evaluation is proven to be effective in measuring students' critical thinking skills. The high level of validity and practicality, plus the interactive and engaging nature of Kahoot!, is able to increase student engagement and facilitate a more effective and enjoyable learning process.